Table Salt Shows Stronger Antibacterial Activity Against Oral Pathogens: Garam Meja Menunjukkan Aktivitas Antibakteri yang Lebih Kuat Terhadap Patogen Mulut - Bima Arya Nugraha; Chylen Setiyo Rini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oral hygiene is necessary to prevent microbial growth, and salt solutions are widely used as natural antibacterial agents. Specific Background: Table salt and Himalayan black salt are commonly used in oral care, but their antibacterial activity at different concentrations requires comparison. Knowledge Gap: Comparative in-vitro evaluation of both salts against oral pathogenic bacteria across multiple concentrations remains limited. Aims: This study compares antibacterial activity of table salt and Himalayan black salt solutions at concentrations of 5%–25% against Streptococcus mutans and Klebsiella pneumoniae using disc diffusion testing. Results: Table salt at 15% produced very strong inhibition against Streptococcus mutans, while Himalayan black salt at 25% showed moderate inhibition. Against Klebsiella pneumoniae, table salt at 20% and Himalayan black salt at 25% demonstrated moderate inhibition. Two-way ANOVA showed significant differences between salt types, while post hoc analysis showed no significant differences among concentrations. Novelty: This study provides graded concentration comparison of two salt types using repeated diffusion testing. Implications: The findings support table salt solution as a natural antibacterial option for oral hygiene and provide laboratory-based reference for natural antimicrobial materials. Highlights: Concentration 15% Solution Produced the Strongest Inhibition Zone Against Cariogenic Bacteria. Diffusion Testing Demonstrated Measurable Bacterial Growth Suppression Across Multiple Treatment Levels. Statistical Comparison Confirmed Distinct Antibacterial Responses Between Both Mineral Solutions. Keywords: Table Salt, Himalayan Black Salt, Streptococcus Mutans, Klebsiella Pneumoniae, Antibacterial Activity